A stillness at Appomattox - Catton, Bruce, 1899-1978. (Garden City, N.Y. : Doubleday, 1953)
The story of the last desperate, cruel year of the Civil War which was made up of an army of mercenaries and embittered veterans.
Includes bibliographical references and index.
Keywords: United States. -- Army of the Potomac; Appomattox Campaign, 1865.; United States -- History -- Civil War, 1861-1865 -- Regimental histories; United States -- History -- Civil War, 1861-1865 -- Campaigns